Neutralization in Aztec Phonology – The Case of Classical Nahuatl Nasals - Kuźmicki, Michał (Research in Language, 2016)
This article investigates nasal assimilation in Classical Nahuatl. The distribution of nasal consonants is shown to be the result of coda neutralization. It is argued that generalizations made for root and word level are disproportionate and cannot be explained through the means of rule-based phonology. It is shown that the process responsible for nasal distribution can only be accounted for by introducing derivational levels in Optimality Theory.